Modeling the selectivity of Diels Alder reactions in various media - Bahadır, Gamze. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
The goal of this research is to model and understand the Diels-Alder and 1,3- dipolar cyclo addition type of reactions in divergent media via two main reactions. In the rst part of this dissertation the exo/endo selectivity for the heterocyclic Diels Alders reaction of the diene, 5-benzylidine-2-arylimino-3-aryl-thiazolidine-4-thione and the dienophile alpha-pinene has been modeled. The mechanism of the reaction has been simulated by using the quantum mechanical method via the B3LYP/6-31+G(d) methodology. The stereoselectivity is investigated for Diels Alder's reaction of a heterocyclic addition reaction including minus alpha-pinene as a dienophile and a diene. The mechanism of the reaction is modeled and the activation energy barriers are calculated. The activation energy barriers are relatively high according to the results of the computational calculations and the reason of not being able to run the experimental reactions is clari ed. The second part of the dissertation aims to investigate the increase of endo selectivity of Diels Alder reactions in ionic liquids. Three main Diels Alder's reactions of cyclopentadiene as a diene and three derivatives of methyl methacrylate as dienophile are simulated in ethanol. The B3LYP/6-31+G(d) level of theory is utilized to model the respective reactions. These reactions have been modeled and the proportion of the endo/exo product ratio for the formation of the products has been calculated. The ratio derived from these calculations is consistent with the experimental results taken from the literature.The ionic liquid e ect to the increase of the endo selectivity is investigated for three reactions. 1-ethyl-3-methylimidazolium chloride is utilized as the ionic liquid. The increase in the formation of the endo product is obtained from the calculations.
Keywords: Diels-Alder reaction.